QUALITY MANAGEMENT AND CONTINUOUS IMPROVEMENT STRATEGIES IN SMALL BUSINESSES - Eshmurodova Sh.Sh. (Journals Park Publishing, 2025)
This article analyzes the issues of effective implementation of quality management and continuous improvement strategies in small businesses. The study highlights how the main principles of the Kaizen philosophy - continuous process improvement, active employee involvement and rational use of resources - can be implemented in small business conditions. It also examines the effectiveness of tools such as the 5S system, the suggestion mechanism and quality circles in small businesses. The results obtained include practical recommendations for small businesses on optimizing costs, improving the quality of products and services, and fully satisfying customer needs.
Keywords: Small business, quality management, continuous improvement, Kaizen, 5S system, suggestion system, quality circles, efficiency.